2015
DOI: 10.1080/19336896.2015.1038018
|View full text |Cite
|
Sign up to set email alerts
|

As a toxin dies a prion comes to life: A tentative natural history of the [Het-s] prion

Abstract: A variety of signaling pathways, in particular with roles in cell fate and host defense, operate by a prion-like mechanism consisting in the formation of open-ended oligomeric signaling complexes termed signalosomes. This mechanism emerges as a novel paradigm in signal transduction. Among the proteins forming such signaling complexes are the Nod-like receptors (NLR), involved in innate immunity. It now appears that the [Het-s] fungal prion derives from such a cell-fate defining signaling system controlled by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In this context, allorecognition systems in fungi have been proposed to originate from broader pathways, evolutionarily related to innate immunity systems of plants and animals ( 14 , 35 , 36 ). It has been speculated that emergence of such allorecognition systems is due to sporadic mutations and subsequent cooptation of genes evolved primarily to mediate heterospecific nonself recognition and detection of modified self ( 37 , 38 ). The rcd-1 locus has undergone extensive genomic rearrangements in the genus Neurospora , which have been proposed to be at the origin of the allorecognition system ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, allorecognition systems in fungi have been proposed to originate from broader pathways, evolutionarily related to innate immunity systems of plants and animals ( 14 , 35 , 36 ). It has been speculated that emergence of such allorecognition systems is due to sporadic mutations and subsequent cooptation of genes evolved primarily to mediate heterospecific nonself recognition and detection of modified self ( 37 , 38 ). The rcd-1 locus has undergone extensive genomic rearrangements in the genus Neurospora , which have been proposed to be at the origin of the allorecognition system ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, except in the specific case of NLRs involved in incompatibility systems the nature of the ligands activating these NLRs are currently unknown. Compared to the two other systems, the NWD2/HET-S is characterized by the fact that this system has been exaptated as an allorecognition system in [Het-s]/HET-S incompatibility [36]. It has been possible experimentally, to derive incompatibility systems analogous to [Het-s]/HET-S from both HELLP and HELLF.…”
Section: Discussionmentioning
confidence: 99%
“…HET-s and HET-S functionally differ in their HeLo domain, a substitution at position 33 deprives HET-S of pore-forming activity. In a sense HET-s can be viewed as a mutant form of HET-S devoid of cell death inducing activity, it is that very property (lack of toxicity associated with the amyloid form) that allows the protein to propagate as a prion in vivo [ 21 ].…”
Section: The Het-s/het-s Systemmentioning
confidence: 99%
“…Note that the incompatibility reaction between [Het-s] and HET-S occurs independently of NWD2. Incompatibility is proposed to derive by exaptation from the NWD2/HET-S system, yet it does not require NWD2 to occur [ 21 ]. Remarkably, it was reported that the N-terminal region of NWD2 and the HET-s PFD can functionally substitute for the Pyrin signaling domains in the human NLRP3 NLR and ASC, its downstream effector.…”
Section: The Nwd2/het-s Paradigmmentioning
confidence: 99%